Parkinson’s disease, dopaminergic drugs and the plant world - Kempster, Peter; Ma, Andrew (Frontiers in Pharmacology, 2022)
A large proportion of drugs used for the treatment of neurological disorders relate to naturally occurring compounds, many of which are plant alkaloids. This is particularly true of Parkinson’s disease (PD). The pharmacopoeia of PD has strong botanical origins, while major discoveries about the neurochemistry of the basal ganglia came from the study of phytochemicals. This article narrates the development of pharmacotherapy for PD in terms of historically important plant-derived substances—tropane and hamala alkaloids, reserpine, levodopa, apomorphine, and ergoline dopamine receptor agonists. Alkaloids are nitrogen-containing secondary metabolic products that tend to be biologically active. They appear to be involved in plants’ adaptation to herbivorous animals, though their exact purpose and the ways in which they work are uncertain. A sizable group of alkaloids influence animal dopaminergic systems, highlighting a key biological relationship. While animals must acquire the energy that plants harness, plants need to engage with the animal attribute that they lack—movement—in order to maximize their reproductive fitness. Neuroactive flowering plant compounds have been interacting with vertebrate and invertebrate motor systems for 100 million years. A deep evolutionary connection helps to explain why the pharmacological treatment of PD is imprinted with the power of these mysterious botanical chemicals.